Transaksi Pihak Terkait atas Biaya Audit: Peran Efektivitas Komite Audit - Kristiyani, Dian (E-Jurnal Akuntansi; Vol 30 No 10 (2020)DO - 10.24843/EJA.2020.v30.i10.p14, 2020)
The purpose of this study is to analyze the effect of related party transaction and the effectiveness of audit committee on audit fee. This research uses samples a  manufacturing company in Indonesia Stock Exchange (IDX) in 2014-2018. The sampling technique used purposive sampling. The total number of companies used as research samples is 118 companies. Using tools SPSS 20 and testing hypothesis using linear regression. The F test indicates a stable and significant model. R square is 58,7 percent. The results show that related party transactions have a significant positive effect and the effectiveness of the audit committee has a significant negative effect on audit fees. Keywords: Related Party Transaction; Effectiveness Of Audit Committee; Audit Fee.